(untitled) (Sciences & Technology. A, exactes sciences, 2014)
A heterogeneous photo-Fenton-like degradation process of 1-naphthol (1-NP) promoted by natural iron oxide (NIO) in the presence of H2O2 was studied under artificial (365 nm) and solar irradiation. This is an important reaction for the environment since both H2O2 and iron oxides are common constituents of natural waters. Furthermore, iron oxides function as catalysts in chemical oxidation processes used with H2O2 for treatment of contaminated waters. The NIO used in this study was characterized by X-ray diffraction (XRD), X-ray fluorescence and Brunauer–Emmett–Teller (BET) methods. The results show that the NIO is a composite material that contains predominantly crystalline hematite particales (Fe2O3). The Fe2O3 in NIO was able to initiate the Fenton-like and photo-Fenton-like reactions. The effects of initial pH, catalyst dosage, H2O2 concentration and the wavelength of the light source (UV and solar) on the photodegradation of 1-NP were investigated. The optimal content of the NIO was 1 g L-1 and the optimal H2O2 concentration was 10 mM. The degradation could occur efficiently over a wide pH range of 3-8.3. Furthermore, an important effect of light was observed. The photo-oxidation of 1-NP in NIO-H2O2 system under solar light was significantly accelerated in comparison with artificial irradiation at 365 nm.